2008
DOI: 10.1289/ehp.10448
|View full text |Cite
|
Sign up to set email alerts
|

Low Phytoestrogen Levels in Feed Increase Fetal Serum Estradiol Resulting in the “Fetal Estrogenization Syndrome” and Obesity in CD-1 Mice

Abstract: BackgroundAlthough estrogenic chemicals can disrupt development of the reproductive system, there is debate about whether phytoestrogens in soy are beneficial, benign, or harmful.ObjectivesWe compared reproductive and metabolic characteristics in male and female mice reared and maintained on non-soy low-phytoestrogen feed or soy-based high-phytoestrogen feed.MethodsThe low-phytoestrogen diet was non-soy PMI 5K96 (verified casein diet), and the high-phytoestrogen diet consisted of soy-based PMI 5008 during preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
2
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 37 publications
11
81
2
2
Order By: Relevance
“…The high levels of fasting glucose combined with elevated circulating insulin, the consequent high HOMA index and the altered ipGTT reflect that removing phytoestrogens from the diet may induce insulin resistance and diabetes. These results are in agreement with other authors (Ruhlen et al, 2008), who reported that 3 months old male rats exposed to a low phytoestrogen diet from gestation presented impaired glucose clearance compared with males fed a phytoestrogen rich diet. Cederroth et al (2008) reported that dietary phytoestrogens improve glucose metabolism via activation of AMPK, a major sensor of energy status.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The high levels of fasting glucose combined with elevated circulating insulin, the consequent high HOMA index and the altered ipGTT reflect that removing phytoestrogens from the diet may induce insulin resistance and diabetes. These results are in agreement with other authors (Ruhlen et al, 2008), who reported that 3 months old male rats exposed to a low phytoestrogen diet from gestation presented impaired glucose clearance compared with males fed a phytoestrogen rich diet. Cederroth et al (2008) reported that dietary phytoestrogens improve glucose metabolism via activation of AMPK, a major sensor of energy status.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, male rats that stopped receiving dietary phytoestrogens in adult life displayed significantly increased adipose tissue and body weights compared to HP fed animals. These results are consistent with Ruhlen et al (2008) and Cederroth and Nef (2009a), who reported that removing phytoestrogens from rodent feed during pregnancy and lactation in CD-1 mice produces an obese phenotype in the litter and impairs glucose tolerance. Our work demonstrates for the first time that if male rats consume phytoestrogens until they reach adult life, when the feed is replaced by a low phytoestrogen diet, an obese phenotype with alterations in glucose metabolism emerges.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Some studies on rats and mice demonstrated increased testicular weight when animals were treated with soy diet or isoflavone supplements during gestation and lactation or continuous exposure, similar to the effect described above in marmosets treated with soy infant formula during infancy (Akingbemi et al, 2007;McVey et al, 2004;Piotrowska et al, 2011;Ruhlen et al, 2008;Wisniewski et al, 2005). Other authors reported a decrease (Atanassova et al, 1999;Wisniewski et al, 2003) or no effect on testicular weight (Fielden et al, 2003;Kang et al, 2002).…”
Section: Effects On Male Reproductive Systemmentioning
confidence: 68%